Evidence for an Instability-induced Binary Merger in the Double-peaked, Helium-rich Type IIn Supernova 2023zkd - A. Gagliano; V. A. Villar; T. Matsumoto; D. O. Jones; C. L. Ransome; A. E. Nugent; D. Hiramatsu; K. Auchettl; D. Tsuna; Y. Dong; S. Gomez; P. D. Aleo; et al. (The Astrophysical Journal)
We present ultraviolet to infrared observations of the extraordinary Type IIn supernova 2023zkd (SN 2023zkd). Photometrically, it exhibits persistent and luminous precursor emission spanning ∼4 yr preceding discovery ( M _r  ≈ −15 mag, 1500 days in the observer frame), followed by a secondary stage of gradual brightening in its final year. Post-discovery, it exhibits two photometric peaks of comparable brightness ( M _r  ≲ −18.7 mag and M _r  ≈ −18.4 mag, respectively) separated by 240 days. Spectroscopically, SN 2023zkd exhibits highly asymmetric and multicomponent Balmer and He I profiles that we attribute to ejecta interaction with fast-moving (1000–2000 km s ^−1 ) He-rich polar material and slow-moving (∼400 km s ^−1 ) equatorially distributed H-rich material. He II features also appear during the second light curve peak and evolve rapidly. Shock-driven models fit to the multiband photometry suggest that the event is powered by interaction with ∼5–6 M _⊙ of CSM, with 2–3 M _⊙ associated with each light curve peak, expelled during mass-loss episodes ∼3–4 yr and ∼1–2 yr prior to explosion. The observed precursor emission, combined with the extreme mass-loss rates required to power each light curve peak, favors either super-Eddington accretion onto a black hole or multiple long-lived eruptions from a massive star to luminosities that have not been previously observed. We consider multiple progenitor scenarios for SN 2023zkd, and find that the brightening optical precursor and inferred explosion properties are most consistent with a massive ( M _ZAMS ≥ 30 M _⊙ ) and partially stripped He star undergoing an instability-induced merger with a black hole companion.